A comprehensive review on anaerobic digestion of organic fraction of municipal solid waste - Zamri M.F.M.A.; Hasmady S.; Akhiar A.; Ideris F.; Shamsuddin A.H.; Mofijur M.; Fattah I.M.R.; Mahlia T.M.I. (Elsevier Ltd, 2023)
Biogas; Greenhouse gases; Hydrolysis; Municipal solid waste; Anaerobic digestion process; Bio-energy; Bio-recovery post-treatment; Biogas reactor; Energy recovery; Nutrient recovery; Organic fraction of municipal solid wastes; Post treatment; Substrate pretreatment; Waste substrates; Anaerobic digestion